2020
DOI: 10.1155/2020/7878656
|View full text |Cite
|
Sign up to set email alerts
|

Study and Simulation Analysis of Vehicle Rear-End Collision Model considering Driver Types

Abstract: The reasonable distance between adjacent cars is very crucial for roadway traffic safety. For different types of drivers or different driving environments, the required safety distance is different. However, most of the existing rear-end collision models do not fully consider the subjective factor such as the driver. Firstly, the factors affecting driving drivers’ characteristics, such as driver age, gender, and driving experience are analyzed. Then, on the basis of this, drivers are classified according to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Traffic safety has become a major public health concern all around the world [1][2][3]. The traffic safety problem is multidimensional, and many risk factors, i.e., technical factors (vehicles), environmental factors (the road and infrastructures), human factors (the road users) and their interactions, contribute to causing crashes [4][5][6]. Generally, two approaches to traffic safety studies have been established so far [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Traffic safety has become a major public health concern all around the world [1][2][3]. The traffic safety problem is multidimensional, and many risk factors, i.e., technical factors (vehicles), environmental factors (the road and infrastructures), human factors (the road users) and their interactions, contribute to causing crashes [4][5][6]. Generally, two approaches to traffic safety studies have been established so far [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the reaction time of the driver in the fatigue state is greater than that in the normal state. e reaction time at different ages varies, and the greatest difference in response time was in the age group 22-45 [19]. Zhang et al divided driving behavior types into five categories: conservative, cautious, conventional, radical, and adventurous [20].…”
Section: Driver Factorsmentioning
confidence: 99%
“…Our previous studies suggested that the driver reaction time is significantly positively relevant with driver fatigue magnitude, which can be quantified into the interval of [0, 10] [19]. More specifically, we consider that the driver fatigue degree is considered as a continuous parameter demonstrating the driver's travelling time on roadway.…”
Section: Driver Factorsmentioning
confidence: 99%
“…Road traffic injuries rank sixth in the world in terms of years of life with disability, according to the World Health Organization [2]. Road safety is studied through different risk factors, such as infrastructure factors (type of road, lighting, pavements), human and behavioural factors (age, gender, actions taken) and vehicle factors (type of vehicle, speed of vehicles), and their interactions allow for a better understanding of the causes of road accidents and their impact on the injury rate of those involved [3,4].…”
Section: Introductionmentioning
confidence: 99%